Synthesis and characterization of biocompatible methacrylated Kefiran hydrogels: towards tissue engineering applications - Radhouani, Hajer (2021)
Hydrogel application feasibility is still limited mainly due to their low mechanical strength and fragile nature. Therefore, several physical and chemical cross-linking modifications are being used to improve their properties. In this research, methacrylated Kefiran was synthesized by reacting Kefiran with methacrylic anhydride (MA). The developed MA-Kefiran was physicochemically characterized, and its biological properties evaluated by different techniques. Chemical modification of MA-Kefiran was confirmed by 1H-NMR and FTIR and GPC-SEC showed an average Mw of 793 kDa (PDI 1.3). The mechanical data obtained revealed MA-Kefiran to be a pseudoplastic fluid with an extrusion force of 11.21 ± 2.87 N. Moreover, MA-Kefiran 3D cryogels were successfully developed and fully characterized. Through micro-CT and SEM, the scaffolds revealed high porosity (85.53 ± 0.15%) and pore size (33.67 ± 3.13 μm), thick pore walls (11.92 ± 0.44 μm) and a homogeneous structure. Finally, MA-Kefiran revealed to be biocompatible by presenting no hemolytic activity and an improved cellular function of L929 cells observed through the AlamarBlue® assay. By incorporating methacrylate groups in the Kefiran polysaccharide chain, a MA-Kefiran product was developed with remarkable physical, mechanical, and biological properties, resulting in a promising hydrogel to be used in tissue engineering and regenerative medicine applications.